Production Costs, Their Content and Description - Urmanbekova Iroda Farkhodovna (Genius Journals, 2022)
Article 7 of the Law of the Republic of Uzbekistan "On Accounting", adopted in the new edition of April 13, 2016, provides thaobjects ”described as. President of the Republic of Uzbekistan Sh.M.In his book "Critical analysis, strict discipline and personal responsibility - should be the daily rule of every leader", Mirziyoyev said: "The first is the effectiveness of targeted programs that show how effective the reforms are. These include the following economic and financial indicators for the development of industry and other sectors: the state of production capacity, reduction of costs and costs, the level of localization and profitability, the unconditional increase in product competitiveness "[2]they did.it should be noted that indicators such as the state of production capacity, costs and cost, the level of localization and profitability, reflected in the accounting reports, are of great importance today. these issues are the main objects of management accounting
Keywords: Production; Republic; Uzbekistan; profitability